Myocysticercosis: an unusual presentation in sternocleidomastoid muscle diagnosed by high frequency ultrasonography - Ilyas, Mohd; Bhat, Arshad (The European Research Journal, 2019)
Myocysticercosis is rare disorder and in particular the involvement of the neck muscles is much rarer. A rare case of myocysticercosis involving the right sternocleidomastoid muscle is presented with ultrasonographic demonstration of the nidus and associated edema.